3D microstructure and anti-oxidation behavior of porous CoAl intermetallic fabricated by rapid thermal explosion. (November 2022) - Shang, Zhichao; Cai, Xiaoping; Jiao, Xinyang; Zheng, Yan; Zhang, Baojing; Pahlevani, Farshid; Feng, Peizhong
Abstract: With the increasing demand for high-temperature gas filtration, porous intermetallic compounds have attracted much attention. In this study, high porosity CoAl with 3D microstructures was prepared using the thermal explosion. The link between the pore structure, mechanical and oxidation resistance of the product was established using 3D-XRM. Moreover, an oxidation corrosion test was conducted in fluid and static air at 700–900 °C for up to 120 h. During the rapid growth stage, the mass gain was dominated by the inward diffusion of O, while during the slow growth stage, it was dominated by the outward diffusion of Al. Highlights: CoAl intermetallic of high porosity (42.24%) were fabricated by rapid TE reaction. 3D structure pores were characterized quantitatively via the pore network model. Acoustic emission was used to predict the variation of CoAl mechanical properties. Al2 O3 film improves the anti-oxidation property of porous CoAl. Mass gain is dominated by the inward diffusion of O and outward diffusion of Al.